Transfer of Task-Probability-Induced Biases in Parallel Dual-Task Processing Occurs in Similar, but Is Constraint in Distinct Task Sets. - Lück, Inga; Mittelstädt, Victor; Mackenzie, Ian G.; Fischer, Rico (Journal of Experimental Psychology. Learning, Memory & Cognition, 2024)
Although humans often multitask, little is known about how the processing of concurrent tasks is managed. The present study investigated whether adjustments in parallel processing during multitasking are local (task-specific) or global (task-unspecific). In three experiments, participants performed one of three tasks: a primary task or, if this task did not require a response, one of two background tasks (i.e., prioritized processing paradigm). To manipulate the degree of parallel processing, we presented blocks consisting mainly of primary or background task trials. In Experiment 1, the frequency manipulation was distributed equally across the two background tasks. In Experiments 2 and 3, only one background task was frequency-biased (inducer task). The other background task was presented equally often in all blocks (diagnostic task) and served to test whether processing adjustments transferred. In all experiments, blocks with frequent background tasks yielded stronger interference between primary and background tasks (primary task performance) and improved background task performance. Thus, resource sharing appeared to increase with high background task probabilities even under triple task requirements. Importantly, these adjustments generalized across the background tasks when they were conceptually and visually similar (Experiment 2). Implementing more distinct background tasks limited the transfer: Adjustmentswere restricted to the inducer task in background task performance and only small transfer was observed in primary task performance (Experiment 3). Overall, the results indicate that the transfer of adjustments in parallel processing is unrestricted for similar, but limited for distinct tasks, suggesting that task similarity affects the generality of resource allocation in multitasking.